MASA KEJAYAAN ISLAM: SEBUAH REFLEKSI - Amin, Muhammad Rais (P3M STAIN Sorong, 2016)
The golden age of Islam (The golden Age) in its various aspects has experienced in recorded history. Abbasid dynasty was victorious in a long enough period of time, starting from the year 132-656 H / 750-1258 AD In the âAbbasids, Islam has made progress in its various aspects, both in the political, military, economic, science, science, culture, civilization and others. But along with the history of human civilization, all aspects of the progress in the end must be terminated with weakness, deterioration and destruction as a dialectical process of history that cannot be avoided by any human being. Abbasid dynasty was not immune from the laws of history. Based on the above, then this article will unravel more about the chronological history of formation, progress, decline and destruction of the Abbasid dynasty.